Race, gender, and religion in the Vietnamese diaspora: the new chosen people - Ninh, Thien-Huong T. (Palgrave Macmillan, 2020)
This book examines how the racialization of religion facilitates the diasporic formation of ethnic Vietnamese in the U.S. and Cambodia, two communities that have been separated from one another for nearly 30 years. It compares devotion to female religious figures in two minority religions, the Virgin Mary among the Catholics and the Mother Goddess among the Caodaists. Visual culture and institutional structures are examined within both communities. Thien-Huong Ninh invites a critical re-thinking of how race, gender, and religion are proxies for understanding, theorizing, and addressing social inequalities within global contexts